Validation of a modified closed circuit, oxygen dilution residual volume method - Johnson, Brenda M. (My University, 1993)
A modified closed circuit, oxygen dilution method for the measurement of residual volume (RV) was compared to the method described by Wilmore (1969). The major difference in equipment was the substitution of a 7 liter calibration syringe and rubber rebreathing bag for the wet spirometer in the original procedure. Duplicate measurements of RV were made with each method in random order of 90 subjects (45 M,45 F) age 18 to 69 (mean = 31 yrs).